Control mechanisms of primary productivity revealed by Calcareous Nannoplankton from marine isotope stages 12 to 9 at the Shackleton Site (IODP Site U1385) - González‐Lanchas, A. (2021)
Nowadays, primary productivity variations at the SW Iberian Margin (IbM) are primarily controlled by wind-driven upwelling. Thus, major changes in atmospheric circulation and wind regimes between the Marine Isotope Stages (MIS) 12 and 9 could have driven substantial changes in phytoplankton productivity which remains poorly understood. We present a high-resolution calcareous nannofossil record from the Shackleton Site Integrated Ocean Discovery Program Site U1385 that allow the assessment of primary productivity and changing surface conditions on orbital and suborbital timescales over the SW IbM. These records are directly compared and integrated with terrestrial – Mediterranean forest pollen – and marine – benthic and planktic oxygen stable isotopes (δ18O), alkenone concentration [C37], Uk´37-Sea Surface Temperature and % C37:4 – proxy records from Site U1385. Our results indicate intra-interglacial increase in primary productivity together with intensification of the Azores anticyclonic high-pressure cell beyond the summer that suggests a two-phase upwelling behavior during the full interglacial MIS 11c (420–397ka), potentially drived by atmospheric NAO-like variability. Primary productivity is largely enhanced during the inception of glacial MIS 10 and the early MIS 10 (392–356ka), linked to intensified upwelling and associated processes during a period of strengthened atmospheric circulation. In agreement with the conditions observed during Heinrich events of the last glacial cycle, primary productivity reductions during abrupt cold episodes, including the Heinrich-type (Ht) events 4 to 1 (436, 392, 384 and 339ka) and the Terminations V and IV, seems to be the result of halocline formation induced by meltwater arrival, reducing the regional upward nutrient transference